2022
DOI: 10.3389/phrs.2022.1604856
|View full text |Cite
|
Sign up to set email alerts
|

Palliative Care Within the Primary Health Care Setting in Australia: A Scoping Review

Abstract: Objectives: This scoping review identifies and details the scope of practice of health professionals who provide palliative care within the primary health setting in Australia.Methods: A scoping review approach was conducted on the Cinahl (Ebsco), Scopus, Medline (Ovid) and PubMed databases to extract articles from 1 December 2015 to 1 December 2020. Broad text words and MeSH headings were used with relevance to palliative care, general practice, primary health, and community setting. Extracted journal article… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 81 publications
0
1
0
Order By: Relevance
“…In addition, the multidisciplinary team revealed, in its majority (93.3%), that the role of APN had a beneficial impact on patient care since it was comprehensive, safe, and met the needs of the patient (23) . In addition, a recent scope review conducted in Australia (24) identified several well-defined nursing roles in the provision of palliative care in primary health settings. With proper training and support, GP nurses can initiate and facilitate conversations about advanced care planning with patients.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the multidisciplinary team revealed, in its majority (93.3%), that the role of APN had a beneficial impact on patient care since it was comprehensive, safe, and met the needs of the patient (23) . In addition, a recent scope review conducted in Australia (24) identified several well-defined nursing roles in the provision of palliative care in primary health settings. With proper training and support, GP nurses can initiate and facilitate conversations about advanced care planning with patients.…”
Section: Resultsmentioning
confidence: 99%